TEACHERS' CHALLENGES IN ASSESSING SPEAKING SKILLS IN EFL CLASSROOMS: A STRUCTURED NARRATIVE REVIEW AND PEDAGOGICAL SYNTHESIS - Inayatul Muntaqiyah; Syifa Zia Muharni; Ali Salim Ali Razaq (Sensei International Journal of Education and Linguistic, 2026)
Assessing speaking is not easy for the teacher because speaking happens directly and cannot be repeated like a written test. Many teachers feel confused about what should be assessed and how to give the score fairly. This article discusses teachers' challenges in assessing speaking skills in EFL classrooms. The method used is literature review from various journals about language assessment. The result shows that the challenges are about deciding the construct, designing the task, making the rubric, keeping the score consistent, and also the time because the class is big. The teacher also feels that they are not trained enough in assessment. Therefore the teacher needs training and the school must give time for the speaking assessment.